Tietz fundamentals of clinical chemistry and molecular diagnostics - Burtis, Carl A.; Bruns, David E., 1941-; Sawyer, Barbara G.; Tietz, Norbert W., 1926- (Elsevier/Saunders, 2015)
Uses a laboratory perspective to provide you with the chemistry fundamentals you need to work in a real-world, clinical lab. This title includes accurate chemical structures to explain the key chemical features of relevant molecules.